MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA MELALUI COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION - Anasrul .; Jarnawi Afgani Dahlan; Anizar Ahmad (Universitas Syiah Kuala, 2013)
The ability of mathematical communication is one of the ability that are required in the curriculum in learning mathematics in school. Weak mathematical communication skills of students is one of the problems in the learning of mathematics in high school that need to be solved . This study aims to examine the ability of mathematical communication between the students who acquire STAD model with conventional learning . This research is an experimental study with a control group study design pre-test post-test . The study population was all students of SMA Negeri 1 Tangan-tangan Class XI , while the sample taken by purposive sampling two classes is class XI IA1 as an experimental and class XI IA2 as the control class. Two kinds of instrument are used to collect the data. They are test and nontest they include the ability of mathematical communication test. While nontest consist of questionnaires of attitude scale and observation sheets. They include the ability of mathematical communication test, while nontes of questionnaires and observation sheets. To see whether the students' mathematical communication skills between gain learning STAD model is better than conventional learning group that used the t-test at the 0.05 significance level after testing prerequisites are fulfilled. Baser on the data and results of statistical tests were analyzed with Microsoft Excel 2007 to interpret students' mathematical communication skills and attitudes of students towards learning model STAD. Based on this research, it is known that: 1) The ability of mathematical communication of studend who acquire cooperative learning STAD model better than students who received conventional teaching; 2) There are differences in mathematical communication skills improvement among subgroups of low, medium and high on student learning using the model STAD so that the learning of mathematics with this model improve mathematical communication skills are not evenly for each subgroup of students. 3) Based on the analysis of attitude scale questionnaire , the students' positive attitudes towards learning mathematics with STAD model. 4) In general, the learning of mathematics by using STAD model makes the students more active in the learning time, students have much opportunity to explore his ability and help each other. 5) Barriers in implementing STAD models namely: the willingness of insufficient time, students' skills in reading comprehension and item is still low .